Fire-induced flow temperature distribution beneath a ceiling - Razieh Khaksari Haddad; Mohammad Rasidi Rasani; Zambri Harun (Penerbit Universiti Kebangsaan Malaysia, 2020)
Many tunnels have been built to reduce traffic volumes in densely populated urban areas. In this research, a series of small-scale experiments were carried out in a 3 m length model tunnel with 0.6 m width and 0.95 m height to examine the temperature distribution along the tunnel ceiling. The containers for the source of the fire in this study were six different sizes of pools filled with n-heptane and gasoline. The smoke maximum temperature has been investigated experimentally and theoretically beneath the tunnel ceiling. A few results are obtained, firstly, dimensional analysis proposed in this research resulted in a theoretical estimation model for predicting maximum gas temperature under the ceiling. Then, the results from theoretical equation were compared with experimental data and an acceptable prediction was presented. The temperature distribution and smoke emission relationship with various ventilation velocities and heat release rate (HRR) were analyzed. The results show that an increase in ventilation velocity leads to temperature decrease and the fire source with higher HRR causes higher maximum smoke temperature. Furthermore, since the maximum temperature and the gas temperature decrease beneath the ceiling of the tunnel during the fire affect the tunnel structure, these parameters were also considered. Experimental results were also compared with that of Kurioka’s model. Empirical correlations for flow temperature decay along the tunnel were also proposed based on experimental data.